1986
DOI: 10.1007/bf01965524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketanserin, a selective 5-HT2 serotonergic antagonist, on the secondary recruitment of human plateletsin vitro

Abstract: Ketanserin, a selective 5-HT2 serotonergic receptor antagonist, reduces in vitro the release-associated human platelet aggregation induced by threshold concentrations of collagen and curtails the second wave of aggregation/release induced by critical concentrations of ADP in particular and, to a lesser extent, of 1-epinephrine. Its inhibitory effect on the second waves becomes more pronounced when the reaction is already attenuated by moderate cyclo-oxygenase inhibition with esculetin, by yohimbine or by propr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…It amplifies platelet aggregation via 5-HT2 receptors, for which ketanserin is a specific antagonist [9]. We found that ethanol considerably ampli fied the action of serotonin in the process of platelet aggregation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It amplifies platelet aggregation via 5-HT2 receptors, for which ketanserin is a specific antagonist [9]. We found that ethanol considerably ampli fied the action of serotonin in the process of platelet aggregation.…”
Section: Discussionmentioning
confidence: 78%
“…It has been suggested that ethanol directly affects the function of blood platelet mem branes and acts indirectly by influencing plasma lipids or by changing the release and synthesis of some arachidonic acid deriva tives [2,5,6). Platelets contain serotonin (5-hydroxytryptamine, 5-HT) which evokes in vitro a reversible aggregation of human blood platelets [7] and amplifies platelet ag gregation in response to various agonists in cluding ADP, adrenaline, noradrenaline, collagen and the calcium ionophore A23187 [8], The amplification of platelet aggrega tion by 5-HT is inhibited by the selective 5-HT2 receptor antagonist ketanserin [9], Our previous studies demonstrated [10] that eth anol inhibits the uptake and enhances the release of 5-HT from rat blood platelets. In vitro, it inhibited the aggregation of blood platelets but did not change the potentiating action of 5-HT on ADP-induced aggrega tion.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of ketanserin (5-HT 2 receptor antagonist) on the second phase of ADP-aggregation wave became more pronounced when the reaction was already attenuated by PRO [25]. Treatment of rabbits with phenoxybenzamine, resulting in decreased number ofreceptors, was found to decrease aggregation both in the presence and absence of PRO [26].…”
Section: In Vitro Studies Bab Drugs and Platelet Aggregationmentioning
confidence: 91%
“…It amplifies platelet aggregation of rats and hu mans via 5-HT2 receptors [7,8], of which a selective antagonist is ketanserin [14], Thus we tried to determine whether the serotoner gic mechanisms play any role in the suppres sion of platelet aggregation evoked by capto pril. In our experiments we demonstrated that captopril, in contrast to ketanserin, did not affect the amplifying effect of 5-HT ( fig.…”
Section: Discussionmentioning
confidence: 99%